162 TRANSTHORACIC ECHOCARDIOGRAPHY PREDICTORS OF LEFT ATRIAL THROMBUS AND DENSE SMOKE IN PATIENTS WITH NONVALVULAR ATRIAL FIBRILLATION. (1st January 2006) - Stoyioglou, A.; Ssennyamantono, B. K.; Marino, N.; Kutnick, R.; Panagopoulos, G.; Goswami, R.; Skipitaris, N. T.; Coplan, N. L.
Abstract : Introduction: Major known risk factors for stroke in nonvalvular atrial fibrillation (NVAF) identified by transesophageal echocardiography (TEE) are left atrial thrombus (LAT), spontaneous echocardiographic contrast (dense smoke), left atrial appendage emptying velocity (LAAEV) less than or equal to 0.2 m/sec, and complex aortic plaque (CAP). Study Hypothesis: Transthoracic echocardiography (TTE) variables may predict the presence of LAT. Methods: Of 183 consecutive patients (median age 73, range 35 to 103 years) who underwent TEE prior to cardioversion for NVAF and who had a TTE within 3 months of the index TEE, 20 were excluded because of mitral valve disease (any mitral stenosis, moderate-severe mitral reurgitation, or mitral prosthesis). The following variables were entered as potential predictors of TEE risk factors for stroke in logistic regression analyses: age $ 70 years, left ventricular hypertrophy (LVH, septum in diastole > 1.2 cm), left ventricular systolic dysfunction (LVSD, LVEF < 50%), presence of right ventricular (RV) pacing lead, and left atrial enlargement (LAE, left atrial diameter > 4.0 cm). Results: The following table presents the results of the logistic regression analyses (n = 163): Conclusion: LVH and LVSD were identified as independent predictors of LAT, dense smoke, and low LAAEV. RV pacing lead was found to be an additional predictor of dense smoke, whereas age $ 70 years was the only predictor of complex aortic plaque.